Acceptability, usability and feasibility of experienced sampling method in chronic secondary pain syndromes - Damci, Aysun; Hoeijmakers, Janneke G. J.; den Hollander, Marlies; Köke, Albère; de Mooij, Marion; Faber, Catharina G.; Verbunt, Jeanine A. M. C. F. (Frontiers in Neurology, 2023)
Background In chronic pain syndromes, symptoms can fluctuate and change over time. Standard questionnaires cannot register these fluctuations. Nonetheless, the experience sampling method (ESM) is developed to collect momentary measurements of everyday complaints, tracing fluctuations in symptoms and disabling factors over time. Although valuable information can be collected in this way, assessment may also be a burden. This study aimed to investigate the acceptability, usability, and feasibility of ESM in chronic secondary pain syndromes, in a single-center study in the Netherlands. Methods A prospective observational study with repeated measurements was conducted in patients with chronic secondary neuropathic and musculoskeletal pain syndromes, including small fiber neuropathy, spinal cord injury, and rheumatoid disorder. Results Thirty-four participants were included and filled in the ESM, of whom 19 were diagnosed with small fiber neuropathy, 11 with spinal cord injury, and 4 with a rheumatoid disorder. The mean age was 54.7 ± 13.9 years (range: 23–77) of whom 52.9% were female. In total, 19 participants filled in the general and user-friendliness evaluation about the acceptability and usability of the ESM. The general evaluation showed no influence of ESM on participants’ social contacts (mean 1.47, SD 1.12), activities (mean 1.74, SD 1.44), and mood (mean 1.89, SD 1.59). The answers options of ESM were a good representation of the experiences of participants (mean 4.58, SD 1.77). Regarding feasibility, the overall response rate for answering the beep signals of ESM was 44.5% in total. The missing rate per person varied from 13% to 97% with a median of 54.1%. Conclusion The general evaluation and the user-friendliness revealed sufficient outcomes in favor of the ESM application. ESM seems a promising measurement tool to use in secondary chronic pain syndromes.